Pentingnya Penanaman Nilai - Nilai Karakter dalam Pendidikan di Era Modern - Tiana Rahmadani; Rizki Fadilah; Juandi Juandi; Setiawati Setiawati (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
This study aims to explain the urgency of instilling character values in education in the modern era, describe the strategies or approaches used in the educational environment, and identify challenges and solutions in their implementation. The method used is qualitative with a descriptive approach. Data collection techniques included observation, in-depth interviews, and documentation, with the research subjects consisting of teachers, students, and principals at primary and secondary education levels. The results show that the cultivation of character values such as honesty, responsibility, discipline, tolerance, and cooperation is very important to form learners who not only excel in academics, but also have moral integrity and emotional maturity. Strategies used in character cultivation include integration of character values in learning, habituation of positive attitudes, teacher role models, and extracurricular activities. The main challenges in implementing character education are the negative influence of digital media, the weak role of the family, and the lack of consistency in character development. Solutions include improving educators' competence in character education, strengthening cooperation between schools and parents, and creating a school environment that supports a positive culture. Thus, character education should be an integral part of the education system, through synergistic cooperation between schools, families and communities.